It is Impossible to Create the Universe without Nonlinear Physics (Global Journal of Science Frontier Research, 2020)
The author predicted that if the Black Holes are anti-matter, they must have hyperboloid shape. Shortly after the prediction a Black Hole was photographed and it had hyperboloid shape. The author further explained that two galaxies (or two Black Holes) would merge only if they have opposite magnetic polarity, which can happen only if they spin in opposite directions. Since the anti-vortices spin counterclockwise and create magnetic field off the anti-vortex, they are the ones that create matter. If so, the Black Holes at the center of the galaxies at the first half of their lifespan, when they are actively making new stars, must spin counterclockwise like an anti-vortex. Since all observed merging of Black Holes, galaxies, and galaxy clusters requires opposite magnetic polarities of the mergers, which means spinning in opposite direction, in the second half of their lifespan, the galaxies and the Black Holes at the center of them must spin clockwise (like vortices). Since vortices suck energy, in the second half of the galaxy lifetime, the galaxy's Black Hole will spin clockwise and attract and swallow the old stars to recycle them and turn them into anti-matter, so that with time new stars can be created in perfect order.
Keywords: nonlinear physic; turbulence; cosmos and turbulence